Medial Habenula-Interpeduncular Nucleus Circuit Contributes to Anhedonia-Like Behavior in a Rat Model of Depression - Xu, Chunpeng; Sun, Yanfei; Cai, Xuewei; You, Tingting; Zhao, Hongzhe; Li, Yang; Zhao, Hua (Frontiers in Behavioral Neuroscience, 2018)
The lateral habenula (LHb) has attracted increasing attention for its role in the pathogenesis of depression. However, the role of the medial habenula (MHb) is poorly understood. The MHb connects to the interpeduncular nucleus (IPN) both morphologically and functionally. The MHb-IPN pathway is important in regulating higher brain functions, including cognition, reward, and decision making. Disruption of these functions is implicated in the pathogenesis of depression. Thus we investigated the role of the MHb-IPN pathway in depression. Our study found that in the chronic unpredictable mild stress (CUMS)-exposed rat model of depression, MHb metabolic activity was increased. MHb-lesions in the CUMS-exposed rat model reversed anhedonia-like behavior as observed in the sucrose preference test (SPT), and significantly downregulated the elevated metabolic activity of the IPN. Substance P (SP)-containing neurons of the MHb innervate the IPN and are the main source of SP in the IPN. The tissue content of SP in the IPN of the CUMS-exposed rats increased, and MHb-lesions reversed this change. In vitro experiment, firing rate recordings showed that SP perfusion increased the activity of IPN neurons. Our results suggest that hyperactivity of the MHb-IPN circuit is involved in the anhedonia-like behavior of depression, and SP may mediate this effect of the MHb on the IPN neurons.